Morphological and semantic analysis of the word "memohon" as an equivalent of "berdoa" in Indonesian - Paramita, Ratri; Zulfan, Muhammad; Tauhid, Booni (Journal of Language and Pragmatics Studies, 2025)
This research focuses to analyse the morphological and semantic structure of the Indonesian word memohon, particularly in its usage as a synonym for berdoa (to pray or to request earnestly). It also explores the possibility that memohon originates from the noun pohon (tree), considering the phonological transformation that typically occurs when the prefix me- is attached to root words beginning with the consonant "p." A qualitative methodology is applied in this study, incorporating both descriptive and analytical analysis. The data of the study are drawn from dictionaries, linguistic references, and relevant Indonesian language corpora. The analysis involves the examination of word formation (morphology), phoneme shifts, and lexical as well as contextual meanings of memohon. The findings reveal that although pohon and memohon may appear phonologically similar, there is no direct etymological connection between them. The verb memohon is derived from the base word mohon, which has long existed in Classical Malay with the meaning of 'to respectfully request.' The prefix me- forms the active verb memohon, commonly used in both formal and spiritual contexts. Therefore, although memohon is often associated with praying, it is not derived from pohon. The study concludes that phonetic similarity alone is insufficient for determining word origins and highlights the importance of etymological evidence in morphological analysis. The findings of this research enhance understanding of the fields of lexicology and semantics in Indonesian, especially concerning the formation and use of spiritually significant verbs.